Analisis Program Pengembangan Sumber Daya Manusia Penyuluhan Pada Dinas Tanaman Pangan Dan Peternakan Distrik Konawe Utara - Ali Imran; Nasrullah Dali; Muh. Nur (STIE AMKOP, 2023)
This study aims to find out and analyze the human resource development program of extension workers through education and the human resource development program of extension workers through training at the Food Crops and Livestock Office of North Konawe Regency. As for the informants in this study, there were five people. The analysis tool used is the Analysis Interactive Model from Miles and Huberman. Based on the results of the study, it can be concluded that (1) The human resource development program for extension workers through education at the Food Crops and Livestock Office of North Konawe Regency is good; (2) The human resource development program of extension workers through training at the Food Crops and Livestock Office of North Konawe Regency is included in the category that is already quite good. Keywords : Human Resource Development, Education and Training